2020
DOI: 10.3390/jcm9061914
|View full text |Cite
|
Sign up to set email alerts
|

The Ovarian Sensitivity Index (OSI) Significantly Correlates with Ovarian Reserve Biomarkers, Is More Predictive of Clinical Pregnancy than the Total Number of Oocytes, and Is Consistent in Consecutive IVF Cycles

Abstract: Background and Objectives: Some biomarkers of ovarian responsiveness to gonadotropins and the total number of retrieved oocytes are known to affect the success rate after controlled ovarian stimulation (COS) and in vitro fertilization (IVF). The aim of this study was to study another putative marker, the Ovarian Sensitivity Index (OSI: (number of retrieved oocytes/total gonadotropin dose) × 1000), assessing whether (a) it correlates with ovarian responsiveness biomarkers, (b) it is an independent predictor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…Embryos that progressed to the expanded blastocyst stage on day 5 (score 3) showed compacted inner cell mass (score 1), and cohesive trophoectoderm (score 1 or 2) were selected for the first transfer in both groups. The ET was performed as previously described [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Embryos that progressed to the expanded blastocyst stage on day 5 (score 3) showed compacted inner cell mass (score 1), and cohesive trophoectoderm (score 1 or 2) were selected for the first transfer in both groups. The ET was performed as previously described [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The following variables were collected for all enrolled patients: age, duration of infertility, BMI, basal AMH, AFC, smoke habit. For all ART treatment cycles, the following variables were registered: type of pituitary suppression (GnRH agonist or antagonist), total FSH dose, serum peak estradiol (E2), number of retrieved oocytes, Ovarian Sensitivity Index (OSI = number of retrieved oocytes/total FSH dose × 1000 [17]), number of mature (MII) oocytes, number of fertilized (2PN) oocytes, number of available embryos, proportion of top-quality embryos (IMCS score > 8/10).…”
Section: Discussionmentioning
confidence: 99%
“…During COH, the extra-physiological dose of GN can promote the growth and development of other follicles, avoid the occurrence of follicular atresia, and stimulate multiple oocytes. Some studies have shown that FSH stimulation at super-physiological doses may promote the growth of the remaining follicles in the follicular pool and contribute to the recruited antral follicles, thus accelerating the depletion of the follicular pool (7). In addition, it has been reported that repeated vaginal puncture of the ovary may lead to the release of ovarian autoantigens, resulting in a decrease in the number of follicles in the follicular pool (8).…”
Section: Discussionmentioning
confidence: 99%
“…In IVF treatment, most patients will receive large doses of GN stimulation and be subjected to repeated surgery for egg harvesting. Whether these treatments have a negative effect on ovarian reserve and responsiveness remains controversial (7,13,14).…”
Section: Discussionmentioning
confidence: 99%